Genome-wide generation and systematic phenotyping of knockout mice reveals new roles for many genes. - White, J; Gerdin, A; Karp, N; Ryder, E; Buljan, M; Bussell, J; Salisbury, J; Clare, S; Ingham, N; Podrini, C; Houghton, R; Estabel, J; et al. (2013)
Mutations in whole organisms are powerful ways of interrogating gene function in a realistic context. We describe a program, the Sanger Institute Mouse Genetics Project, that provides a step toward the aim of knocking out all genes and screening each line for a broad range of traits. We found that hitherto unpublished genes were as likely to reveal phenotypes as known genes, suggesting that novel genes represent a rich resource for investigating the molecular basis of disease. We found many unexpected phenotypes detected only because we screened for them, emphasizing the value of screening all mutants for a wide range of traits. Haploinsufficiency and pleiotropy were both surprisingly common. Forty-two percent of genes were essential for viability, and these were less likely to have a paralog and more likely to contribute to a protein complex than other genes. Phenotypic data and more than 900 mutants are openly available for further analysis. PAPERCLIP: